I’dadu Mawad Ta’lim al-Lughah al-‘Arabiyyah li al-Dirasah al-Idhafiyah ‘ala al-Mustawa al-Jami’i li Tanmiyah al-Maharaat al-Lughawiyah: Dirasah Halah fi Ma’had Namira al-‘Ali Lamongan - Ahmad Afandi (Al-Wazan: Journal of Arabic Education, 2023)
The book used in the teaching activities at the Nimrah Higher Institute of Lamongan is the Arabic “بين يديك سلسلة في تعليم اللغة العربيىة لغير الناطقين بها".” Likewise, in this institute, it included factors in the education process, such as the presence of the educational curriculum, the educational book, and the calendar.  However, in this institute, the level of students’ understanding of the lessons is different, especially in the Arabic language. Some of them are superior to everyone else, and some of them are moderate, and some of them need additional help outside the classroom in order for everyone to understand the lesson.  Therefore, the researcher prepares additional educational materials that help develop the four language skills. As for the research method, it is the developmental method for analyzing and explaining the data and results in the effectiveness of using the educational book. The research is conducted on the design of the pre and post test. As for the result of the research, the preparation of educational materials in teaching the Arabic language at the Namira Higher Institute for Additional Study is well prepared by the researcher, as the additional book goes through many design, arbitration, correction, modification, then field experience, and finally the final production, which is the additional book. The additional book for the development of the four skills at Namira Higher Institute Lamongan is good, as the result of the students after teaching the book is higher than before the education, and that is because the average result of the students in the pre-test is 67.8125%, and when the post-test is in the percentage of 89.625%.  Likewise, the number of "t arithmetic" is greater than the number of "t table", which is 9,156. Depending on those results obtained by the students in the pre and post test, the result of the (t-test), and the result of the questionnaire, it was found that the additional book designed to develop the four language skills at Namira Higher Institute Lamongan is effective.  It has a positive effect on the development of language skills.